Evaluation of di‐calcium malate, used as a novel food ingredient and as a source of calcium in foods for the general population, food supplements, total diet replacement for weight control and food for special medical purposes. (6th June 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present scientific opinion deals with the evaluation of the safety of di‐calcium malate (DCM) proposed as a novel food ingredient and as a source of calcium for use in foods for the general population, food supplements, total diet replacement for weight control and food for special medical purposes (FSMP), and with the bioavailability of calcium from this source. The structural formula of the proposed complex is based on expert judgement and not supported by any analytical data. On the basis of the available data, the Panel concluded that there was insufficient scientific evidence of a difference between the proposed novel food ingredient named as di‐calcium malate (DCM) and calcium malate already authorised as a source of calcium included in Annex II to Directive 2002/46/EC. Accordingly, the Panel was unable to assess the safety of DCM as a novel food ingredient. On the basis of the results provided, the Panel considered that DCM does not completely dissociate into calcium and malic acid. The Panel concluded that when DCM dissociates, calcium would be available following ingestion of DCM and the bioavailability would appear similar to values reported for other sources of calcium already permitted. Furthermore, the Panel concluded that on the basis of the information available it was not possible to calculate the exposure to DCM as a source of calcium to foods for the general population, food supplements, total diet replacement for weight control and FSMP.